Determination of OPAC acceptance by campus library users through the TAM model - Nugraha, Muhammad Rai Dzikri; Barmawi, Mira Musrini (Hexatech: Jurnal Ilmiah Teknik, 2026)
This study examines user acceptance of library information systems based on the Online Public Access Catalog (OPAC) by employing the Technology Acceptance Model (TAM) framework. The research focuses on identifying the key determinants influencing technology acceptance, particularly Perceived Ease of Use and Perceived Usefulness, and how these constructs shape users’ attitudes, behavioral intentions, and actual system usage. Data were collected through a structured questionnaire distributed to active library users. The findings reveal that TAM provides a strong explanatory foundation for understanding the relationships among the variables. Perceived ease of use significantly enhances perceived usefulness, which subsequently fosters positive attitudes, strengthens users’ intentions to use the system, and ultimately leads to actual utilization of the OPAC. These results offer comprehensive insights into the factors that drive the acceptance of library information systems and affirm the relevance of TAM as an evaluative model for academic information services.